PROYEK PENANGGULANGAN KEBIJAKAN PENANGANAN KEMISKINAN DI PERKOTAAN - Taurusman Situmeang (REFORMASI, 2013)
Poverty was the structural problem and multidimensional, included the dimension of politics, social, economics and assets. To deal it, the government launched heterogeneous programs. These implications of the existence of the programs often helped increased income the grass root community. However since the monetary crisis and economics that struck Indonesia in 1997, happened the jump of the level of the unemployment. The impact more far emerged the increase in poverty in urban areas. This showed awareness of the need empowered the poor community. P2KP was the program of poverty alleviation, with strategy that is different to programs beforehand. The P2KP program strategy was strengthened institutional the community. Institutional soundness was needed in the constructive framework of the community organisation that really could become the poor effort forum, that autonomous, could be continuous and influence the process of decision making that was linked with the public policy in local level. The community organisation that was built by and for the community, further will be believed to manage the P2KP fund in a participative manner transparent and accountable.